The Signification of the Copula in Fernando de Enzinas’ Syncategoremata - Pérez-Ilzarbe, Paloma (Vivarium, 2015)
This article deals with a brief difficultas in the Tractatus de compositione propositionis mentalis by Fernando de Enzinas: qualiter copule significent tempus et an copule de presenti et preterito sint synonime. A progressive determination of the signification of the copula is analysed: first, Enzinas defines his position about the principal syncategorematic signification of the copula; then, he analyses the sense of the consignification of time traditionally attributed to the copula. The originality of Enzinas’ position is highlighted, given the fact that he gives preference to the question as to how the copulae signify time rather than the question as to which time the copulae signify.